Physiological, anatomical and ultrastructural effects of aluminum on Styrax camporum, a native Cerrado woody species - Bressan, Anna C. G. [UNESP]; Silva, Giselle S. [UNESP]; Banhos, Otavia F. A. A. [UNESP]; Tanaka, Francisco A. O.; Habermann, Gustavo [UNESP] (Springer Nature, 2020)
Styrax camporum Pohl. (Styracaceae) is a woody species that grows on acidic soils from the Brazilian savanna with high aluminum (Al) saturation (m% > 50%), where it accumulates ~ 1500 mg Al per kg dry leaves. Using nutrient solution, a previous study showed that 1480 μM Al causes toxicity symptoms, which raises the question whether less than 1480 μM Al could cause beneficial effects on this species. Here, we checked possible altered gas exchange rates, damage to organelles in root tips and the association between Al exposure and mitochondria occurrence in cells of root tips, once organic acids from Krebs cycle exuded by the roots of this species when exposed to Al have been recently evidenced. Five-month-old plants were grown in nutrient solution with 0, 740 and 1480 μM Al for 90 days. Plants exposed to 1480 μM Al showed less developed root system, reduced plant height and low gas exchange rates in relation to those exposed to 0 and 740 μM Al, confirming that 1480 μM Al is toxic to S. camporum. However, plants exposed to 0 and 740 μM Al had similar number of leaves, plant height, root biomass, root length, total plant biomass and gas exchange rates, indicating that no beneficial effects from 740 μM Al could be noted on this species. In plants exposed to 0 and 740 μM Al, mitochondria were noted at the root tip, while at 1480 μM Al these organelles were not evident due to the conspicuous vacuolation of root cells. S. camporum shows limited tolerance to Al in nutrient solution. In addition, this species is not dependent on Al to grow and develop because the plants grew well under 0 and 740 μM Al.
Keywords: Al3+; Anatomical analysis; SEM; Styracaceae; TEM